Teaching philosophy in practice: Developing compatibility through personal practical knowledge - Kumagai, Kazuaki; Black, Laurel Johnson (Universitas Pendidikan Indonesia, 2018)
As part of an MATESOL mentoring program, developing educators were paired with experienced professors.Â The authors explore how personal practical knowledge bridges the gap between teaching philosophy and classroom practice. The complex layers of experience and knowledge that a mentor can offer need to be prompted, however; they cannot simply be deduced by observing. Using observational notes, interviews, and reflection, we explore real-time teaching decisions as a way to elaborate and reconsider the usually succinct teaching philosophy statement. This is particularly important for new teachers and those who are teaching in contexts or with students whose culture is still being absorbed. Personal practice knowledge is seen as the stem from which both teaching philosophy and classroom practice bloom.